May 1940 : the battle for the Netherlands - Amersfoort, H. (Hermanus), 1951-; Kamphuis, P. H. (History of warfare, 2010)
"In May 1940, the Netherlands were overrun by German armed forces. The five-day campaign might seem to be a prime example of Blitzkrieg, which led shortly afterwards to the rapid and unexpected overthrow of France. This book, based on the newest scholarly research, argues that this is too simple a view. Even though the German assault on the Netherlands made use of tanks, aircraft and airborne troops, it was still a classic campaign against a weak opponent in a theater on the margins of Fall Gelb. In many instances, artillery and infantry were the decisive factors and it is debatable whether the bombing of Rotterdam can be seen as a precursor to the aerial terror campaigns against civilian populations that marked the later stages of the Second World War"--Page 4 of cover